Development and characterization of bioactive glass: Preliminary study for medical applications. (2022) - Meechoowas, Ekarat; Naknikham, Usuma; Tungsanguan, Ornuma; Martvijit, Suchanun; Pamok, Cheevapat; Tapasa, Kanit
Abstract: This research aims to study the morphology of bioactive glass nanoparticles synthesis by using sol-gel process and the bioactivity mechanism in in-vitro study, which can be used in medical application. Two bioactive glasses, 70SiO2 :30CaO2 (BGN) and 70SiO2 :15CaO2 :15CuO (Cu-BGN), were prepared with tetraethoxysilanes (TEOS, SiC8 H20 O4 ), calcium nitrate tetrahydrate (Ca(NO3 )2 ) and copper (II) nitrate hemi-pentahydrate (Cu2 H10 N4 O17 ). As received-samples were white and blue powder for BGN and Cu-BGN, respectively. The morphology of bioactive glass nanoparticles was examined by the scanning electron microscope (SEM) showing the spherical shape and homogeneity particles with the average size around 330–400 nm of BGN sample while, Cu-BGN was smaller, around 160–260 nm. The X-ray diffraction spectra of both compounds were amorphous after calcination at 700 °C. Moreover, Cu-BGN demonstrated to the peaks of copper oxide and quartz. In the meantime, bioactivity was studied by using in-vitro method. The glass powders were immersed in simulated body fluid (SBF) solution for 3, 6, 24 h, and 4 days. The XRD peaks of both glasses at 2θ = 20° shifted to 30° which represented characteristic peak of the hydroxyapatite. However, this was not confirmed by the fourier transform infrared (FTIR) spectroscopic because of the results were shown only the Si-O-Si asymmetric/symmetric stretching. Obtaining well homogeneous nanoparticles and amorphous bioactive glass in this study could be applied to develop the glass composition with higher bioactivity.